Weightlifting-related injuries - Jonathan David Rajaratnam Peter; I Putu Adiartha Griadhi (DiscoverSys Inc., 2020)
Background: Each year, more and more athletes partake in weightlifting, aiming to outperform their predecessors and achieve new records of feats of strength. However, even despite the newer knowledge of biomechanics, and the safety precautions taken to prevent injury, such events still do take place.Aim: The study aims to determine the sources of these injuries, as well as the more frequent parts of the body that get injured, those more prone to it.Conclusion: The numerous injuries that can be sustained during weightlifting has been noted including its causes, as well as its effect on an individual and the incidence rate of the occurrence in professional weightlifters.